Reporting the Official Truth: The Revival of the FCC's News Distortion Policy - Lili Levi (Washington University Law Quarterly, 2000)
This Article seeks to expand the current debate over broadcasters’ obligations by examining the news distortion doctrine and ultimately proposing that it be eliminated. In sum, the reinvented news distortion doctrine would undermine the very democratic norms marshaled in its defense. Particularly in light of the complex relation between news and the exercise of democratic citizenship, we should hesitate to support a regulatory policy that effectively grounds government censorship on an unrealistic view of news production.
Keywords: Press; Freedom of the press; United States. Federal Communications Commission; Broadcast journalism